Further data on the occurrence of Leprosa milga Kirn & La Salle on Eucalyptus in southern Italy (Hyrnenoptera Eulophidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
This eulophid has been recently described as new species of a new genus on the basis of specimens from South Africa and Italy; although no specimen has been found in Australia, it is considered original from this continent; anyhow, it exhibits a huge invasive power and is parthenogenetic as other eulophids occurring on Eucalyptus. A list of the specimens collected in southern Italy from 2004 to 2007 is given. Many females were found on branches of E. camaldulensis in July; many others emerged in the laboratory from samples of seed capsules of the same plant from August to October; at last, a minor number of females was obtained from closebuds in September. Observations show presence of L. milga females to be more abundant in summer, when Eucalyptus trees bear developing buds. Because these buds will open in the next summer, they can be regarded as a probable substrate for oviposition and larval development.
Keywords: Eucalyptus camaldulensis; invasive eulophid; supposed life-cycle